2022
DOI: 10.3390/app12094094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the Microbiome in Cancer Diagnostics and Therapeutics by Creating and Utilizing ML Models

Abstract: Recent studies have highlighted that gut microbiota can alter colorectal cancer susceptibility and progression due to its impact on colorectal carcinogenesis. This work represents a comprehensive technical approach in modeling and interpreting the drug-resistance mechanisms from clinical data for patients diagnosed with colorectal cancer. To accomplish our aim, we developed a methodology based on evaluating high-performance machine learning models where a Python-based random forest classifier provides the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Some could benefit from Short Term Scientific Mission (STMS) grants (16 in total) to work with research teams in different countries on ML4Microbiome-related projects with the view to publish the results of their activities in peer-reviewed journals. 8 In terms of publication output, to date ML4Microbiome members have published work on specific ML applications for particular diseases, such as Cancer Diagnostics and Therapeutics (Cekikj et al, 2022), classification of patients with Celiac Disease (Arcila-Galvis et al, 2022), Coronary Artery Disease Risk Prediction (Vilne et al, 2022), novel paradigms in human gut microbiome metabolism (Bidkhori et al, 2021), Parkinson's disease (Rosario et al, 2021), Type 2 Diabetes (Ruuskanen et al, 2022), oral and related gut diseases (Di Stefano et al, 2023), along with systematic or scoping reviews on ML applications on microbiome data (Tonkovic et al, 2020;Marcos-Zambrano et al, 2021) and its challenges and solutions (Moreno-Indias et al, 2021) of which all are available from the complete list of the Action's publications on the ML4Microbiome website.…”
Section: Community Building Networking and Training: The Three Key To...mentioning
confidence: 99%
“…Some could benefit from Short Term Scientific Mission (STMS) grants (16 in total) to work with research teams in different countries on ML4Microbiome-related projects with the view to publish the results of their activities in peer-reviewed journals. 8 In terms of publication output, to date ML4Microbiome members have published work on specific ML applications for particular diseases, such as Cancer Diagnostics and Therapeutics (Cekikj et al, 2022), classification of patients with Celiac Disease (Arcila-Galvis et al, 2022), Coronary Artery Disease Risk Prediction (Vilne et al, 2022), novel paradigms in human gut microbiome metabolism (Bidkhori et al, 2021), Parkinson's disease (Rosario et al, 2021), Type 2 Diabetes (Ruuskanen et al, 2022), oral and related gut diseases (Di Stefano et al, 2023), along with systematic or scoping reviews on ML applications on microbiome data (Tonkovic et al, 2020;Marcos-Zambrano et al, 2021) and its challenges and solutions (Moreno-Indias et al, 2021) of which all are available from the complete list of the Action's publications on the ML4Microbiome website.…”
Section: Community Building Networking and Training: The Three Key To...mentioning
confidence: 99%
“…In addition, we noticed that in the whole group of patients a high abundance of Veillonellaceae was correlated with shorter PFS, which seems to be in line with the results of Song et al [ 70 ]. Moreover, Cekikij et al indicated that patients with CRC non-resistant to ICIs therapy had an increased content of Akkermansia , Clostridium sensu stricto 1 and Oscillospiraceae and decreased content of Streptococcus and Leuconostoc [ 77 ]. Due to the fact that PFS is not the best indicator of the effectiveness of immunotherapy, our 47 advanced NSCLC patients with microbiome genotyping are under surveillance in order to obtain prospective long-term observations in terms of overall survival.…”
Section: Our Own Observations On the Relationship Between The Gut Mic...mentioning
confidence: 99%